PROCEDIMENTOS PARA PREENCHIMENTO DE FALHAS EM SÉRIES CLIMÁTICAS NO ESTADO DE PERNAMBUCO - Silva, Lívia Maria Cavalcante; Bezerra, Fabiano Simplicio; Vasconcelos, Maria Catiana de; Silva, Madson Rafael Barbalho da; Santos, Ana Cláudia Davino dos; Almeida, Ceres Duarte Guedescabral de (IRRIGA, 2021)
GAP FILLING PROCEDURES OF CLIMATOLOGICAL SERIES IN THE STATE OF PERNAMBUCO LÍVIA MARIA CAVALCANTE SILVA1; FABIANO SIMPLICIO BEZERRA1; MARIA CATIANA DE VASCONCELOS1; MADSON RAFAEL BARBALHO DA SILVA1; ANA CLÁUDIA DAVINO DOS SANTOS1; CERES DUARTE GUEDES CABRAL DE ALMEIDA2 1 Agricultural Engineering Department, Federal Rural University of Pernambuco (UFRPE), St Dom Manuel de Medeiros, s/n, Dois Irmãos, CEP 52171-900, Recife, PE, Brazil, e-mail: cavalcants.livia@gmail.com; fabianoagro14@gmail.com; katiana.vasconcelos22@gmail.com; madsonbarbalhoagronomo@gmail.com; aclaudiadavino@gmail.com 2 Agricultural College Dom Agostinho Ikas (CODAI), Federal Rural University of Pernambuco (UFRPE), Av. Dr. Francisco Correia, 643, Centro, CEP 54735-000, São Lourenço da Mata, PE, Brazil, ceres.cabral@ufrpe.br 1 ABSTRACT This study aimed to compare the applicability of three methods of filling gaps in rainfall and temperature data from thirteen automatic weather stations (AWS) in the state of Pernambuco, from January to December 2019. The methods used were arithmetic mean, regional weighting, and simple linear regression. The data estimated by filling techniques have been subjected to comparison using R² and descriptive statistical analysis. The estimated data of air temperature presented R2 equal or very close to 1 for the three methods. On the other hand, the estimated data of rainfall showed values similar or closer to the real data only to regional weighting (R² = 1) and linear regression (R² = 0.99) methods. The smallest values of standard deviation (1.70) for temperature were obtained with linear regression. The regional weighting method and unfilled data showed greater uniformity for precipitation. The analyzed methods to estimate the climatic variables, air temperature, and precipitation, on a monthly scale, were efficient to fill in missing data in the evaluated AWS. The simple linear regression method is more efficient and adequate, followed by regional weighting, to fill in missing data in climate databases. Keywords: meteorology, automatic weather stations, rainfall, air temperature. SILVA, L. M. C.; BEZERRA, F. S.; VASCONCELOS, M. C.; SILVA, M. R. B.; SANTOS, A. C. D.; ALMEIDA, C. D. G. C. PROCEDIMENTOS PARA PREENCHIMENTO DE FALHAS EM SÉRIES CLIMÁTICAS NO ESTADO DE PERNAMBUCO 2 RESUMO Objetivou-se com este estudo comparar a aplicabilidade de três métodos de preenchimento de falhas de dados pluviométricos e de temperatura oriundos de treze estações meteorológicas automáticas (AWS) no estado de Pernambuco, no período de janeiro a dezembro de 2019. Os métodos utilizados foram média aritmética, ponderação regional e regressão linear simples. Os dados estimados pelas três metodologias foram submetidos à comparação por meio de R² e análise estatística descritiva. Para temperatura do ar, os dados estimados apresentaram R2 igual ou muito próximo de 1 para os três métodos. Por outro lado, os dados estimados de precipitação pluviométrica foram semelhantes ou mais próximos dos dados reais somente para os métodos de ponderação regional (R² = 1) e regressão linear (R² = 0,99). Os menores valores de desvio padrão (1,70) para a temperatura foi obtido com regressão linear. O método ponderação regional e os dados não preenchidos apresentaram maior uniformidade para precipitação. Os métodos analisados para estimar as variáveis climáticas, temperatura do ar e precipitação, em escala mensal, foram eficientes para preenchimento de dados faltantes nas AWS avaliadas. O método regressão linear simples mostra-se mais eficiente e adequado, seguido de ponderação regional, para preenchimento de dados faltantes em bancos de dados climáticos. Palavras-chave: meteorologia, estações meteorológicas automáticas, precipitação pluviométrica; temperatura do ar.